A TRACER STUDY OF PHD IN EDUCATIONAL ADMINISTRATION GRADUATES: RECOMMENDATIONS TO STRENGTHEN THE PROGRAM - Pentang, Jupeth T.; Bautista, Ronalyn M.; Gamozo, Mary Jane D. (LPPM Universitas Jambi, 2024)
This study aims to evaluate the effectiveness and relevance of a PhD in Educational Administration program at a State University in Western Philippines through a tracer study, offering insights into the graduates’ demographic and academic profiles, career alignment, and recommendations for improvement. The study employed a descriptive research design, collecting data from 19 non-randomly selected graduates based on availability. Data were gathered using an instrument based on guidelines from the Philippine Commission on Higher Education, with additional elements drawn from previous tracer studies. Analytical tools such as frequency counts, percentages, and arithmetic means were used to describe the findings. Results highlight that the PhD in Educational Administration program effectively serves mid-career professionals, attracting individuals from diverse backgrounds and helping them meet evolving leadership demands in educational administration. Graduates reported that the program equipped them with the necessary skills to excel in their current roles. However, they suggested several areas for improvement, including enhancing the program's accessibility and inclusivity. These recommendations are crucial to ensuring the program remains relevant, especially in preparing leaders capable of addressing modern challenges in education. This research provides new insights into the strategic role of tracer studies in shaping the future of educational leadership programs. It aligns with Sustainable Development Goal 4 (Quality Education) by proposing a continuous curriculum review, which ensures the program evolves alongside educational leadership trends. The study also underscores the importance of equipping faculty with current insights to strengthen the program's ability to prepare leaders for a dynamic educational landscape.